HUBUNGAN KENAIKAN NILAI UPAH MINIMUM REGIONAL (UMR) DENGAN NILAI UPAH PEKERJAAN BORONG DALAM KEGIATAN KONSTRUKSI BANGUNAN GEDUNG - Andi Purnomo (TEKNISIA, 2016)
Nowadays, the dynamic progresses of industry often collides with its own labors because of many issues, one of them is the monthly salary. Actually Government has released a rule that regulate the minimum increasing of regional allowance annually,called UMR. The rule also applies to the building construction that is usually paid based on the volume of workload or unit price that increases periodically. Building construction project is usually well planned, including its labor payment. However at the same period, both the government regulation and project planning is being held, and this has raised curiosities in terms of its relevance, therefore the objective of this study is to determine the relevance of the annual increasing of the minimum regional sallary (UMR) with the increasing of the unit price. Then, in the budget project planning (RAB), a designer could use the government regulation of minimum allowances to calculate the increasing of labor cost. Actually, the government released another regulation consist of procedures for calculation of unit price of land for buildings and housing standard (SNI) to calculate the cost by volume of works, but its still need the daily workers payment that’s very varied in every group of workers.The research method was collecting annual regulation released by the government and interviewing with a few foreman about their unit price that was stated on the working contract (SPK). The result of this study indicate that there is no relevance between the increasing of minimum regional sallary of it and the increasing of the unit price. Therefore, designers should make item by item volume cost to create budget project planning perfectly or use government standard to state maximum unit price in each volume of works.